Rationalizing Russia's Decision to Host 2018 FIFA World Cup (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
This study aims to determine the advantages that Russia managed to get when it hosted the 2018 FIFA World Cup, using descriptive qualitative methods. As the host of the world's biggest sporting event, Russia is under a lot of pressure from the international community because of the racism issue. Therefore, Russia is trying to take advantage of the opportunities for its role as the host of the 2018 FIFA World Cup, to maximize the benefits that will be obtained. By using the Rational Actor Model and Nation Branding, an analysis of the rationalization of Russia's profits identified, among others: the creation of jobs for 220 thousand Russians, managed to reap a total tourism sector profit of 38.06 billion USD, and at the same time Russia was able to change the country's bad image. by successfully attracting approximately one million foreign tourists who visited directly to watch the World Cup. Key Words : FIFA World Cup 2018, Nation Branding, Rational Actor Model, Russia